1143 Predictors of Duct Dependent Congenital Heart Disease in Infants Transferred by Newborn Emergency Transport Service (NETS) Victoria. (October 2012) - Gupta, N; Kamlin, COF; Stewart, M; Cheung, M; Patel, N
Abstract : Background: Duct dependent congenital heart disease (DDCHD) may be difficult to distinguish from other diagnoses, notably persistent pulmonary hypertension (PPHN). Affected infants born in regional hospitals require transfer to a tertiary paediatric centre for echocardiographic diagnosis. Identification of predictive factors to distinguish DDCHD would assist in appropriate early management during transport. Aims: To describe transport of infants with suspected DDCHD and investigate early predictors of DDCHD. Methods: A retrospective study of infants with suspected DDCHD/PPHN transferred by NETS. Clinical, physiological and investigation data were compared between DDCHD and non-DDCHD (including PPHN) groups. Results: Of 142 eligible infants, 81 had DDCHD and 61 had non-DDCHD, of whom 51 had PPHN. There was no significant difference in median gestation, birth weight, sex, or distance of transfer between DDCHD and non-DDCHD groups. DDCHD infants were more often transferred by air than land. At univariate analysis, presence of heart murmur, abnormal pulses, upper and lower limb BP difference > 10 mmHg, cardiomegaly, initial SpO2 of < 92% and pre-post ductal SpO2 difference > 10% were significantly associated with DDCHD. Labile SpO2, abnormal lung parenchyma, mean blood pressure < 40 mmHg, pH < 7.25, lactate > 5, PaO2 < 50 mmHg and FiO2 > 0.5 were significantly associated with non-DDCHD. On multivariate analysis, only labile SpO2 and mean BP <40 mmHg were significantly associated with non-DDCHD. Conclusion: Labile saturations and mean BP<40 mmHg at the time of referral were significantly associated with non-DDCHD/PPHN. Other clinical features and physiological measures did not distinguish DDCHD from non-DDCHD.